Empowerment of parents in the neonatal intensive care unit by neonatal nurses - Adene Herbst; Carin Maree (AOSIS, 2006)
Parents of infants who are admitted to the neonatal intensive care unit (NICU) need to be empowered to improve bonding, attachment and care-giving skills. Opsomming Ouers van babas wat in die neonatale intensiewesorgeenheid (NISE) opgeneem word, moet bemagtig word met dieoog op bevordering van binding, 'n hegte band met die babas en versorgingsvaardighede. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.